Estimando o desalinhamento cambial brasileiro: Um análise de robustez a partir do modelo global com mecanismo de correç\~ao de erros - Emerson Fernandes Marçal (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper aims to compare two different methodologies to estimate exchange rate misalignment. The first methodology consists in using multivariate time series techniques and a model with domestic variables. The second methodology consists in Pesaran's Global Vector Error Correction Model with global factors (GVECM). The Brazilian case is analyzed using these two methodologies. The results of exchange misalignment estimative are different particularly in their magnitude terms not in their signs. Both methodologies suggests that the channel throughout terms of trade affect exchange rate is indirect. Improvements in Brazilian terms of trade induces improvement in net foreign investment position by affecting current account result. These improvements also induce a real exchange rate appreciation in the long run. In recent period this channel appears to play an important role in explaining Brazilian exchange rate fundamental improvement. The results from GVECM suggest that the level of Brazilian real exchange rate is linked to the level of real exchange of its main trading partners.
Keywords: F31; C32; 330; GVECM; cointegration